FACTORS INFLUENCING THE CHOICE OF RECORD KEEPING AMONG POULTRY FARMERS IN EKITI STATE, NIGERIA - Adedapo, A. O.; Adekunmi, A. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2019)
The importance of poultry keeping cannot be overemphasized due to its contributions to rural households’ food security. Despite the importance of poultry keeping, majority of poultry farmers keep farm records in traditional ways while some did not keep farm records. It was on this basis that the study examined the factors influencing the choice of record keeping among poultry farmers in Ekiti State. The study describe the socio-economic characteristics of the respondents, types of record kept, frequency of record keeping and the methods of record keeping. A well-structured questionnaire was employed to elicit information from 160 poultry farmers using a multi-stage sampled technique. The data collected was analyzed using descriptive statistics, regression analysis and a 3 points Likert scale. It was found that majority (85.56%) of the respondents were male, married (90.00%), educated (71.90%), small scale farmers (90.63%) and mostly within the active age range of 41–50 years with the mean age of 42 (±10.24) years, and average family size of 5 people. Most (71.88%) of them were full-time poultry farmers with average farming experience of 13 (±8.54) years and mean monthly income of ₦296,750.00 (±195,050). The most common type of record kept by the farmers was production record (70.00%). The main reasons for record keeping were profit evaluation (x̅=2.88), planning and budgeting (x̅=2.84), to monitor feed consumption, mortality and theft (x̅=2.80), staff management (x̅=2.79), indication for the validity of farm business (x̅=2.66), expansion of farm size (x̅=2.64), for proper decision making (x̅=2.62), to provide correct data or information for researchers and tax or insurance purpose (x̅=2.53). However, the flock size (P≤0.01), level of education (P≤0.05), years of farming experience (P≤0.05), and access to credit facilities (P≤0.1) were the factors influencing the choice of record keeping among poultry farmers in Ekiti State. Therefore, the stated hypothesis was rejected. Thus, record keeping among poultry farmers is important for monitoring and evaluation of poultry farming.